3x+9=6x+(3)

Simple and best practice solution for 3x+9=6x+(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9=6x+(3) equation:


Simplifying
3x + 9 = 6x + (3)

Reorder the terms:
9 + 3x = 6x + (3)
9 + 3x = 6x + 3

Reorder the terms:
9 + 3x = 3 + 6x

Solving
9 + 3x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
9 + 3x + -6x = 3 + 6x + -6x

Combine like terms: 3x + -6x = -3x
9 + -3x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
9 + -3x = 3 + 0
9 + -3x = 3

Add '-9' to each side of the equation.
9 + -9 + -3x = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 3 + -9
-3x = 3 + -9

Combine like terms: 3 + -9 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| (2x-9)=(27-4x) | | Y^5/y^3 | | 7*5*(2-3)=x | | jp=irt | | -2(12-12n)=6(2n-10) | | 5(3d-2)+4d=2(2d+1)-3d | | 0=2+2x-4x^2 | | (2x-9)-(27-4x)=180 | | 2r+(5-r)=13+2r | | 5y+y=-14 | | -10=5a | | -3(-4w+1)+15=13w | | 5(x+1)+7=7x | | sr+t=u | | 14=-l/4 | | 19= | | -6(b+7)=-7b-37 | | -3(-4w+1)+15=13 | | 4=2(u-4)-8u | | 12.48+0.11=13.23+0.09 | | 8x-4y=-20 | | 21+2(21+3)+(4*21-5)=c | | 6-8(1+6x)=-2-4x | | 1/2(-2)= | | -5(-17-13d)=-4(10-15d) | | 5(2n-4)-3=-36-3n | | -36-4a=-4(8a-5) | | 4x+3+4x=-15 | | 0=-8m^2-2m+2 | | -15s=-75 | | -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) | | x-(12)=-4 |

Equations solver categories